Experiences of transitioning between settings of care from the perspectives of patients with advanced illness receiving specialist palliative care and their family caregivers: A qualitative interview study. (January 2022) - Guo, Ping; Pinto, Cathryn; Edwards, Beth; Pask, Sophie; Firth, Alice; O'Brien, Suzanne; Murtagh, Fliss EM
Background: Transitions between care settings (hospice, hospital and community) can be challenging for patients and family caregivers and are often an under-researched area of health care, including palliative care. Aim: To explore the experience of transitions between care settings for those receiving specialist palliative care. Design: Qualitative study using thematic analysis. Setting/participants: Semi-structured interviews were conducted with adult patients ( n = 15) and family caregivers ( n = 11) receiving specialist palliative care, who had undergone at least two transitions. Results: Four themes were identified. (1) Uncertainty about the new care setting. Most participants reported that lack of information about the new setting of care, and difficulties with access and availability of care in the new setting, added to feelings of uncertainty. (2) Biographical disruption. The transition to the new setting often resulted in changes to sense of independence and identity, and maintaining normality was a way to cope with this. (3) Importance of continuity of care. Continuity of care had an impact on feelings of safety in the new setting and influenced decisions about the transition. (4) Need for emotional and practical support. Most participants expressed a greater need for emotional and practical support, when transitioning to a new setting. Conclusions: Findings provide insights into how clinicians might better negotiate transitions for these patients and family caregivers, as well as improve patient outcomes. The complexity and diversity of transition experiences, particularly among patients and families from different ethnicities and cultural backgrounds, need to be further explored in future research.